Development of a Novel Bioreactor for Efficient Conversion of Agricultural Waste to Renewable Energy - Pouros, Francesca (International Journal Papier Advance and Scientific Review, 2023)
This article describes the creation of an innovative bioreactor for the effective generation of sustainable energy from agricultural refuse. In this research, the design and operation principles of the bioreactor, the selection and preparation of agricultural refuse materials, and the performance of the bioreactor in terms of its effectiveness, energy production, and the quality of the resulting methane are analyzed and evaluated. The performance of the bioreactor was evaluated by employing a variety of feedstocks, inoculum concentrations, and operating temperatures. Based on the research and comparison of the collected data, it was discovered that certain feedstocks, greater inoculum concentrations, and higher operating temperatures led to improved methane production and quality. The results of this research offer important new perspectives on the possibility of an innovative bioreactor for the environmentally responsible management of agricultural refuse and the generation of renewable energy. Additional study is required to perfect the bioreactor’s architecture, as well as to determine whether or not it can be scaled up and whether or not it is economically viable.